THE ROLE OF THE CONCEPT OF ‘CHINA’S PEACEFUL RISE IN CHINA'S FOREIGN POLICY: EVOLUTION AND IMPACT (1993-2013) - АЛІЄВ, Гамідулла (Київський національний університет імені Т. Шевченка, 2025)
Abstract. This article analyses the evolution of the foreign policy of the People's Republic of China (PRC) in the late 20th and early 21st centuries, focusing on the concept of ‘peaceful rise’ (later ‘peaceful development’) as a key element of China's foreign policy strategy during this period. The study covers the reigns of Jiang Zemin (1993-2003) and Hu Jintao (2003-2013), analysing their foreign policy initiatives, economic reforms and influence on the geopolitical positioning of the PRC. The article examines key aspects of the concept of ‘peaceful rise,’ the subsequent transition to the concept of ‘peaceful development,’ and assesses the concept's impact on the formation of China's foreign policy strategies, its main theoretical foundations, and practical implications for China's global integration.

Анотація. Дана стаття присвячена аналізу еволюції зовнішньої політики Китайської Народної Республіки (КНР) у період кінця XX - початку XXI століття, з акцентом на концепцію "мирного піднесення" (пізніше "мирного розвитку") як ключового елемента зовнішньополітичної стратегії Китаюпротягом цього періоду. Дослідження охоплює період правління Цзян Цземіна (1993-2003) та Ху Цзіньтао (2003-2013), аналізуючи їхні зовнішньополітичні ініціативи, економічні реформи та вплив на геополітичне позиціонування КНР. У статті розглядаються ключові аспекти концепції «мирного піднесення», подальший перехід до концепції «мирного розвитку», а також оцінюється вплив концепції на формування зовнішньополітичних стратегій КНР, її основні теоретичні засади та практичні наслідки для глобальної інтеграції Китаю.
РОЛЬ КОНЦЕПЦІЇ «МИРНОГО ПІДНЕСЕННЯ» У ЗОВНІШНІЙ ПОЛІТИЦІ КИТАЮ: ЕВОЛЮЦІЯ ТА ВПЛИВ (1993-2013)
Keywords: peaceful rise; geopolitical positioning; “one country; two systems”; peaceful development; diplomatic interaction; геополітичне позиціонування; «одна країна; дві системи»; мирний розвиток; дипломатична взаємодія; КНР; концепція "мирного піднесення"; "мирний розвиток"; "одна країна; дві системи"